Trabajadoras inmigrantes en Santiago de Chile en los años ochenta - Szasz, Ivonne (El Colegio de México A.C., 1992)
Chile's early process of economic restructuring and trade liberalization allows us to analyze the effects that these processes have had on the labor force and migration patterns during a fifteen year period. One specific sector of the labor force -women migrant workers in Santiago- is particularly interesting to analyze given the disadvantageous conditions of the labor market prevalent during the 1960's.The first years of economic restructuring, which began in Chile during 1975, and the crisis initiated in 1982, provoked a severe increase in poverty and intensified social inequalities. During the last years of economic restructuring -from 1984 on- Chile underwent a period of economic growth and a decrease in unemployment, without, however, experiencing a significant change in the existing levels of poverty. As a result, social inequalities became even stronger. Proof of these disparities is found in the condition of women in the labor force, and is further intensified in the case of migrant women. Among the impacts brought about by economic restructuring most affecting the women who migrated to Santiago we may highlight: the dramatic transformation in domestic service, the increase in the number of non-migrant, lower class women participating in the economy, and the limited and precarious status of women's employment in the more dynamic sectors of the economy.